Design of Hierarchical NiCo@NiCo Layered Double Hydroxide Core–Shell Structured Nanotube Array for High‐Performance Flexible All‐Solid‐State Battery‐Type Supercapacitors. (11th January 2017) - Liu, Yan; Fu, Nianqing; Zhang, Guoge; Xu, Ming; Lu, Wei; Zhou, Limin; Huang, Haitao
Abstract : A novel hierarchical nanotube array (NTA) with a massive layered top and discretely separated nanotubes in a core–shell structure, that is, nickel–cobalt metallic core and nickel–cobalt layered double hydroxide shell (NiCo@NiCo LDH), is grown on carbon fiber cloth (CFC) by template‐assisted electrodeposition for high‐performance supercapacitor application. The synthesized NiCo@NiCo LDH NTAs/CFC shows high capacitance of 2200 F g −1 at a current density of 5 A g −1, while 98.8% of its initial capacitance is retained after 5000 cycles. When the current density is increased from 1 to 20 A g −1, the capacitance loss is less than 20%, demonstrating excellent rate capability. A highly flexible all‐solid‐state battery‐type supercapacitor is successfully fabricated with NiCo LDH NTAs/CFC as the positive electrode and electrospun carbon fibers/CFC as the negative electrode, showing a maximum specific capacitance of 319 F g −1, a high energy density of 100 W h kg −1 at 1.5 kW kg −1, and good cycling stability (98.6% after 3000 cycles). These fascinating electrochemical properties are resulted from the novel structure of electrode materials and synergistic contributions from the two electrodes, showing great potential for energy storage applications. Abstract : Hierarchical nickel–cobalt@nickel–cobalt layered double hydroxide nanotube arrays with separated tubes and massive top are designed and fabricated by facile electrodeposition. The as‐prepared electrode possesses numerous electroactive sites, a highly conductive Ni/Co metallic core, and a high capacitance NiCo layered double hydroxide shell. The assembled battery‐type supercapacitor exhibits superior gravimetric capacitance, good rate performance, high specific energy, and high power density.